Rapid diagnosis of Aspergillus flavus infection in acute very severe aplastic anemia with metagenomic next-generation sequencing: a case report and literature review - Kang, Ying; Zhang, Xiaojing; Qin, Cao; Zheng, Yafeng; Gai, Wei; Jia, Xiaofei; Shao, Bo; Zhang, Shuai; Jiang, Hao; Huang, XiaoJun; Jia, Jinsong (Frontiers in Medicine, 2024)
Infection remains the leading cause of mortality in severe aplastic anemia (SAA) patients, with invasive fungal infections being the great threat. Aspergillus fumigatus accounts for most of the reported fungal infection cases. Here, we present a case of A. flavus infection in a patient with acute very severe aplastic anemia (VSAA) despite persistently negative clinical fungal tests. The patient was admitted to the hospital due to pancytopenia presisting for over a month and intermittent fever for 10 days. Elevated inflammatory indicators and abnormal lung imaging suggested infection, prompting consideration of fungal involvement. Despite negative results from multiple blood, sputum fungal cultures and the serum (1,3)-β-D-glucan/ galactomannan tests. Metagenomic nextgeneration sequencing (mNGS) on multiple blood samples, alongside clinical symptoms, confirmed A. flavus infection. Targeted antifungal treatment with liposomal amphotericin B and voriconazole significantly ameliorated pulmonary symptoms. Additionally, this study reviewed and compared the symptoms, diagnostic approaches, and treatments from prior Aspergillus infections in AA patients. It emphasizes critical role of early mNGS utilization in diagnosing and managing infectious diseases, offering insights for diagnosing and treating fungal infections in VSAA.